Biosynthesis of porphyrins in Rhodopseudomonas palustris-VI. The effect of metals, thiols and other reagents on the activity of uroporphyrinogen decarboxylase - Koopmann, G.E. (1987)
1. 1. The effect of several metals and reagents on the decarboxylation rate of uroporphyrinogen I by using a 16-fold purified preparation of Uroporphyrinogen Decarboxylase from Rhodopseudomonas palustris, was studied. 2. 2. 1 mM Hg2+ and Cu2+ were strong inhibitors, 1 mM Zn2+ and Fe2+ under certain conditions and 1 mM Fe3+ and Cr3+ also inactivated the enzyme, but Pb2+, Cd2+, and Al3+ did not. Metals inhibition was reversed by 1 mM GSH or CvSH. 3. 3. 0.1 mM DTNB and PCMB, 1 mM pyridoxal phosphate and 100 mM chloral hydrate, as well as 1 mM 2-methoxy-5-nitrotropone and 0.2 mM diethylpyrocarbonate inhibited Uroporphyrinogen Decarboxylase; while GSH, CySH, N-ethylmaleimide, sodium thioglycolate, 1,4-dithioerythritol, EDTA and O-phenantroline did not modify activity. 4. 4. Data obtained would indicate that one cysteine, one or two histidine residues and probably a lysine group are required for enzyme activity. © 1987.